Differences in 1-methylcyclopropene sorption dynamics in fresh-cut apple, avocado and tomato fruits. (15th January 2019) - Dong, Xiaoqing; Rao, Jingping; Zhu, Shouliang; Huber, Donald J.
Highlights: Fresh-cut apple, avocado and tomato fruits show different 1-MCP sorption properties. Sorption was high with apple, moderate with avocado, and negligible with tomato fruit. Sorption by fresh-cut apple was strongly suppressed by ascorbate and high temperature. Avocado sorption was unaffected by ascorbate and moderately affected by heat. The results have implications regarding the use of 1-MCP with fresh-cut fruits. Abstract: Fresh-cut (FC) apple, avocado and tomato fruits were examined to determine if sorption dynamics previously reported for FC apple were of general occurrence for other fruits. Fresh-cut apple consumed headspace 1-MCP at high rates, fully depleting 1-MCP in 1.5 h. FC apple pretreated with ascorbate showed 80% reduction in sorption rate. Fresh-cut avocado showed moderate sorption, depleting 95% of system 1-MCP over 6 h. FC avocado was unaffected by ascorbate. FC tomato showed negligible sorption of 1-MCP. Sorption by FC apple and avocado was differentially affected by heat. High-temperature pretreatment of FC apple and avocado resulted in 80% and 20% reductions in 1-MCP sorption rates, respectively. The data indicate that 1-MCP sorption differs significantly between FC tissues of different fruits, likely reflecting differences in thermo-tolerant, physical-sorption processes versus oxidative metabolism. Possible drawbacks in the use of 1-MCP as a post-processing treatment for FC fruits are discussed.